Islamic Scholar and Regional Development: Analyze on Sinan’s Contribution in Civil Engineering - Mohd. Khalid, Halimi; Zainatul Nadra Zainol, Nur; Ahmad, Shakila; Hisyam Mohd Abdul Rahim, Mohd; Shakor Borham, Abdul (International Journal of Engineering and Technology, 2018)
Muslims have been at the top of the glory of civilization with a combination of excellence achieved in the East and West. To the east, the progress made in Kufa, Baghdad and Damascus is a turning point towards the propagation of Islamic civilization. While on the west, Sicilian control has opened the eyes of the world. While the success achieved in Andalusia cannot be matched at that time by other European powers. Almost 14 centuries of Islam dominated the world stage. The development achieved in the aspects of science, architecture, science, technology and so on can not be matched at that time by any external force. This shows that the Islamic government has never forgotten the development aspect, but it is one of the important aspects of civilization. Among this achievement were contributed by Islamic scholar in Ottoman Empire such as Yusuf Sinauddin bin Abdul Mennan or Abdullah. He recognized as Miâ€™mar Sinan. This article aims to analyze the contribution of Sinan in regional development which was focusing in field of civil engineering. It involved content analysis as method for collecting the data. The result shows Sinan had significant contribution in two aspects namely in the construction of water aqueducts and bridges engineering. He also embedded the Islamic attributes in his works.Â Â Â